Refractory Sarcoidosis: A Review - El Jammal T; Jamilloux Y; Gerfaud-Valentin M; Valeyre D; Sève P (Dove Medical Press, 2020)
Thomas El Jammal,1 Yvan Jamilloux,1 Mathieu Gerfaud-Valentin,1 Dominique Valeyre,2 Pascal Sève1,3 1Department of Internal Medicine, Lyon University Hospital, Lyon, France; 2Department of Pneumology, Assistance Publique - Hôpitaux de Paris, Hôpital Avicenne et Université Paris 13, Sorbonne Paris Cité, Bobigny, France; 3Hospices Civils de Lyon, Pôle IMER, Lyon, F-69003, France, University Claude Bernard Lyon 1, HESPER EA 7425, Lyon F-69008, FranceCorrespondence: Pascal SèveService de Médecine Interne, Groupement Hospitalier Nord, 103 Grande rue de la Croix-Rousse, Lyon F-69004, FranceTel +33 426 732 636Fax +33 426 732 637Email pascal.seve@chu-lyon.frAbstract: Sarcoidosis is a multi-system disease of unknown etiology characterized by granuloma formation in various organs (especially lung and mediastinohilar lymph nodes). In more than half of patients, the disease resolves spontaneously. When indicated, it usually responds to corticosteroids, the first-line treatment, but some patients may not respond or tolerate them. An absence of treatment response is rare and urges for verifying the absence of a diagnosis error, the good adherence of the treatment, the presence of active lesions susceptible to respond since fibrotic lesions are irreversible. That is when second-line treatments, immunosuppressants (methotrexate, leflunomide, azathioprine, mycophenolate mofetil, hydroxychloroquine), should be considered. Methotrexate is the only first-line immunosuppressant validated by a randomized controlled trial. Refractory sarcoidosis is not yet a well-defined condition, but it remains a real challenge for the physicians. Herein, we considered refractory sarcoidosis as a disease in which second-line treatments are not sufficient to achieve satisfying disease control or satisfying corticosteroids tapering. Tumor necrosis alpha inhibitors, third-line treatments, have been validated through randomized controlled trials. There are currently no guidelines or recommendations regarding refractory sarcoidosis. Moreover, criteria defining non-response to treatment need to be clearly specified. The delay to achieve response to organ involvement and drugs also should be defined. In the past ten years, the efficacy of several immunosuppressants beforehand used in other autoimmune or inflammatory diseases was reported in refractory cases series. Among them, anti-CD20 antibodies (rituximab), repository corticotrophin injection, and anti-JAK therapy anti-interleukin-6 receptor monoclonal antibody (tocilizumab) were the main reported. Unfortunately, no clinical trial is available to validate their use in the case of sarcoidosis. Currently, other immunosuppressants such as JAK inhibitors are on trial to assess their efficacy in sarcoidosis. In this review, we propose to summarize the state of the art regarding the use of immunosuppressants and their management in the case of refractory or multidrug-resistant sarcoidosis.Keywords: refractory sarcoidosis, JAK inhibitors, anti-TNF